Is the maternal health voucher scheme associated with increasing routine immunization coverage? Experience from Bangladesh - Sultana, Nazia; Hossain, Aazia; Das, Hemel; Pallikadavath, Saseendran; Koeryaman, Mira; Rahman, Mohammad; Chowdhury, Asiful Haidar; Bhuiya, Abbas; Mahmood, Shehrin Shaila; Hanifi, S. M. A. (Frontiers in Public Health, 2023)
Bangladesh initiated the Maternal Health Voucher Scheme (MHVS) in 2007 to improve maternal and child health practices and bring equity to the mainstream of health systems by reducing financial and institutional barriers. In this study, we investigated whether the MHVS has an association with immunization coverage in a rural area of Bangladesh. Between 30 October 2016 and 15 June 2017, we carried out a cross-sectional survey in two low performing areas in terms of immunization coverage- Chattogram (erstwhile Chittagong division) and Sylhet division of Bangladesh. We calculated the coverage of fully immunized children (FIC) for 1151 children aged 12–23 months of age. We compared the coverage of FIC between children whose mothers enrolled in MHVS and children whose mother did not. We analyzed immunization coverage using crude odds ratio (OR) and adjusted OR (aOR) from binary logistic regression models. The overall coverage of FIC was 86%. Ninety-three percent children whose mothers were MHVS members were fully immunized whereas the percentage was 84% for the children of mothers who were not enrolled in MHVS. Multivariate analysis also shows that FIC coverage was higher for children whose mothers enrolled in MHVS compared to those children whose mothers did not; the aOR was 2.03 (95% confidence interval 1.11–3.71). MHVS provides a window for non-targeted benefits of childhood vaccination. Providing health education to pregnant mothers during prenatal care may motivate them to immunize their children. Programmes targeted for mothers during pregnancy, childbirth and post-natal may further increase utilization of priority health services such as childhood immunization.